(untitled) (Fiep Bulletin - online, 2017)
Although the National Sanitary Service has limits, its political, economic and institutional sustainability and theemergence of the demanding subject in the Italian society are facts. In Brazil, in contrast, we experiment the negation of such facts,besides a process of incipient and fragile citizenship. In this sense, this epistemic matrix of patient/demanding subject, elaborated byIvan Cavicchi, is opportune to think about the subject of AB, NASF and SUS good clinic, as far as it widens the sociological healthhorizon and it stimulates the historical patience.